2019
DOI: 10.1177/0018726719875494
|View full text |Cite
|
Sign up to set email alerts
|

Engaged yet excluded: The processual, dispersed, and political dynamics of boundary work

Abstract: What happens when people try to ‘transcend’ organizational boundaries and engage with so-called outsiders? Current boundary-work literature does not fully account for the processual, dispersed, and political dynamics triggered by such efforts. To address this shortcoming, this article builds on an ethnographic study of a professional care provider’s attempts to engage local citizens within one of its care homes. We analyze how actors negotiate the parameters of outsider engagement – that is, how they interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…Hence, our study showed that to unite perspectives of patients and practitioners, it is essential to be aware of possible boundaries that might be encountered to respond adequately. Our study acknowledged that boundary work is a process, dispersed and also political 36 . Identifying and addressing boundaries is a time‐consuming process: it is necessary to give stakeholders enough time to become familiar with research agenda setting and each other's perspectives.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, our study showed that to unite perspectives of patients and practitioners, it is essential to be aware of possible boundaries that might be encountered to respond adequately. Our study acknowledged that boundary work is a process, dispersed and also political 36 . Identifying and addressing boundaries is a time‐consuming process: it is necessary to give stakeholders enough time to become familiar with research agenda setting and each other's perspectives.…”
Section: Discussionmentioning
confidence: 97%
“…We acknowledged that dynamics between insider‐outsider groups (patients versus practitioners) are shaped by multiple boundaries rather than by one single boundary, 36 , 37 and we therefore decided not to address single boundaries in isolation from each other. To illustrate this point, the research agenda setting served as a boundary object that unites the perspectives of patients and practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…More in particular, we argue that balancing inclusion efforts with excluding effects they bring along forms an intrinsic political aspect of stakeholder engagement. This also raises questions on how facilitators of inclusion processes can engage in mitigating the trade-offs and dynamics of exclusion that participatory processes inevitably bring along, as well as the need to more explicitly specify which actors or institutions bear which accountabilities for which process in complexity (e.g., Glimmerveen et al 2020 ) and how responsibility for and political accountability of transdisciplinary processes and outcomes, can be embedded in transdisciplinary practice and design (see also De Campos et al 2017 ; Genus and Stirling 2018 ).…”
Section: Discussion and Reflections: Navigating The Politics Of Transformationmentioning
confidence: 99%
“…The balancing act thus is a tricky one: inclusion requires boundary construction to ensure autonomy and inclusion, while transformation requires boundaries to be deconstructed to engage and transform the complex ‘outer world’, adding an additional layer of complexity to the already highly political nature of boundary work (Brown and Dillard 2015 ; Glimmerveen et al 2020 ). Navigating these two critical functions simultaneously requires reflexive agency of coordinators to manage and enact multiple but, selectively permeable, boundaries of the Labs.…”
Section: Analysis: Unraveling Political Balancing Acts Of Doing Inclusionmentioning
confidence: 99%
“…The ongoing negotiation and re-arrangement of professional boundaries, and hence social order, does not mean that 'everything goes' (Whittle and Housley, 2017 (Housley and Fitzgerald, 2002). Thus, an ethnomethodologically oriented boundary work perspective allows consideration of the complex combinations of divisiveness, permeability, rigidity and fluidity of professional boundaries, which warrant more attention (Glimmerveen et al, 2019).…”
Section: Boundary (Re-)arrangement As Practical Reasoning About Categorisationmentioning
confidence: 99%